Urgensi Peran Perpustakaan dalam Mendukung Proses Pembelajaran di Perguruan Tinggi - Habib Habib (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2018)
An academic library has many significant roles, which includes providing students with resources for their study and research needs and promoting the reading culture. This article focused on three main areas, i.e. academic library management, higher education’s learning process, and the need for the library to support teaching-learning programs. It is concluded that a library does not merely collect resources, but also meets the students’ needs for learning and research supports. The teaching-learning process in the higher education system is closely related to the learning strategies and methods, the quality of lecturers, and students and university’s facilities which includes libraries. Nowadays, many libraries have transformed into students’ main learning resources together with the teaching staff. In this context, the libraries have evolved as a place where students can improve their knowledge. In order to maximize its services, libraries need to continuously improve their management practices.